Borges y la máquina kafkiana de leer - Fernando Limeres Novoa (Svět Literatury, 2023)
The objective is to analyze the Borgesian use of the work of Kafka as a reading device: as a series of texts that work to read others and, on the other hand, to establish the reason why the Argentine has selected Franz Kafka for this function.